Trajetórias do fazer e perder a casa: riscos e temporalidades nas periferias paulistas - Mallak, Fernanda Kagan (2022)
This thesis reflects on the lives of people who experience evictions and forced displacements in the outskirts of São Paulo, mobilizing and articulating three analytical categories: house, risk, and time. From an ethnographic perspective, the field research was conducted in the neighbourhood of Jundiapeba, a peripheral territory of the city of Mogi das Cruzes (SP), where hundreds of houses were built under electricity transmission lines, between high voltage towers. In the year 2018, part of the families was removed through a repossession action requested by the electricity transmission company, in a lawsuit based on 'risk of death of the residents' and the 'risk to regular power supply for the collective'. With the aim of understanding the effects produced by evictions on the practical dynamics of making and losing a house, as well as on the production of territories and cities, the study follows two pathways: the first is about reconstructing the life trajectories of a family, in the voice of three women who experienced the loss of their homes; the second is about following up the actions and mobilizations for housing that took place after the repossession. In the dispute between permanence and removal, these stories are articulated by the myriad of actions legitimated and guided by risk. In the context of imminently losing the house, it was possible to trace the temporalities in the production of documents, the negotiations, the power relations, the infinite waits, and the hope. The study reflected on the (re)production of spaces in cities based on the mapping and fusion of elements and processes that are usually captured separately, such as urban and social policies, management and government, financialization and privatization. In this sense, it proposes a change in analytical perspective, suggesting a diagram of intelligibility of urban land conflicts that starts, first, from the investigation of everyday practices, of the life trajectories of families, from inside and close, to then understand the processes of transformation in urban planning.